2019
DOI: 10.1016/j.freeradbiomed.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The redox biology of redox-inert zinc ions

Abstract: Zinc(II) ions are redox-inert in biology. Yet, their interaction with sulfur of cysteine in cellular proteins can confer ligandcentered redox activity on zinc coordination sites, control protein functions, and generate signalling zinc ions as potent effectors of many cellular processes. The specificity and relative high affinity of binding sites for zinc allow regulation in redox biology, free radical biology, and the biology of reactive species. Understanding the role of zinc in these areas of biology require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
136
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(140 citation statements)
references
References 204 publications
(221 reference statements)
1
136
0
3
Order By: Relevance
“…Zn 2+ as a component of some antioxidant enzymes contributes to reducing excessive ROS generation in several cells and neurons 38 . Free Zn 2+ has apoptosis and oxidant actions via accumulation in the mitochondria for neurons 27 . Hence, intracellular free Zn 2+ depletion causes decrease in mitochondria ROS generation, caspase activities and [Ca 2+ ] i concentrations via increase of rGSH and GPx antioxidant levels in the renal collecting duct cells 45 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zn 2+ as a component of some antioxidant enzymes contributes to reducing excessive ROS generation in several cells and neurons 38 . Free Zn 2+ has apoptosis and oxidant actions via accumulation in the mitochondria for neurons 27 . Hence, intracellular free Zn 2+ depletion causes decrease in mitochondria ROS generation, caspase activities and [Ca 2+ ] i concentrations via increase of rGSH and GPx antioxidant levels in the renal collecting duct cells 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicated that an increase of intracellular free Zn 2+ concentration induces excessive ROS generation 27,28 . After the finding observable increase in the intracellular ROS generation in the SH-SY5Y cells, we suspected increase of the intracellular free Zn 2+ concentration.…”
Section: Hypx-induced Fluorescence Intensity Of Free Zinc Ion (Zn2 + mentioning
confidence: 99%
See 1 more Smart Citation
“…Für mehr als 300 Enzyme ist das Spurenelement eine essenzielle Komponente für deren katalytische Wirkungen. Zink übt strukturelle Wirkungen auf verschiedene Transkriptionsfaktoren aus und reguliert Hormone, Hormonrezeptoren und die Genexpression [3][4] [5]. Es ist essenziell für die angeborene und erworbene Immunität sowie enzymatischer Cofaktor in der Regulation des Kohlenhydrat-, Fett-und Eiweißstoffwechsels [3][5] [6].…”
Section: Funktionen Von Zinkunclassified
“…On the other hand, zinc can induce cellular effects by modulating the activity of transcription factors [33] and phosphatases [34]. Moreover, zinc can influence protein and cellular redox status due to its potential pro-antioxidant or pro-oxidant roles [35,36]. Therefore, the interactions between zinc and vimentin in vitro and in cells can be complex, and their delineation requires careful assessment.…”
Section: Introductionmentioning
confidence: 99%